Use of music as an intervention tool for comfort in patients hospitalized in adult intensive care unit: a look of the multidisciplinary team (Research, Society and Development, 2023)
Introduction: this is a field research, which was carried out by residents of the 2nd year of the Multidisciplinary Program in Intensive Care. Objective: to report the impacts of music therapy in the clinic of critically ill patients. Methodology: music from loudspeakers throughout the sector was used, during the morning and afternoon, in different Intensive Care Units. Results: the detailed analysis of the data allowed observing a decrease of 8 mmHg in systolic blood pressure and 5 mmHg in diastolic blood pressure, however, it did not show significance in the Student's t test. Discussion: it was possible to observe that the participants felt comfortable expressing their emotions, and most described the moment as something relaxing, relaxed and moving, favoring coping with hospitalization. Conclusion: the importance of humanized care is highlighted even in an environment considered hostile.